PENAMPILAN PRODUKSI TELUR PUYUH PADA KAPASITAS KANDANG YANG BERBEDA - Eddy Trjana Sujdani (Universitas Islam Balitar, 2016)
The aim the research was to know the egg production quail ’s to the different cage capacity. The result of this research can be used to inform of people on egg production quail ’s to the different cage capacity. The materials of the reseach use 135 quail, cage system size 50 cm x 50 cm front height 16 cm and back height 12 cm. The research condcted by Completely Randomized Design (CRD) which is consist of three treatment and three replication and be continued Different Small Reallity (DSR). This research show that the cage capacity not significantly effect on production full fill by 20 quail; 15 quail; 10 quail production egg 348, 304,351; 264, 252, 229; 156, 196, 193 and also gave not significanlya effect, and the rate feed are 9390, 9370, 9410; 7380, 7260, 7160; 4760, 4880, 4950 gave not significantly effect.Key word: Quail, egg production, cage capacity